Peran Bimbingan Konseling dalam Pencegahan Fenomena Child Grooming - Nadya Ramadinah; Latiffa Amanda Putri Nur; Dwi Erma Nadhifa; Wahdania Wahdania; Rizki Novirson; Resti Okta Sari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Child grooming is a form of non-physical sexual abuse that involves gradual emotional manipulation, often making it difficult to detect. It typically begins with the abuser gaining the child’s trust and gradually introducing inappropriate behavior, with the goal of sexual exploitation. This study aims to explore the phenomenon of child grooming and the crucial role of guidance and counseling in preventing and managing such cases. The method employed is a literature review, analyzing various relevant scientific articles and research studies. The findings indicate that child grooming is influenced by several factors, including individual traits, family dynamics, and the use of digital media, which has become an increasingly prevalent platform for such abuse. Victims of grooming often experience significant psychological and social consequences, including trauma, emotional distress, and difficulty in forming healthy relationships. Guidance and counseling services are essential in the prevention, early detection, and intervention in grooming cases. These services provide support for both potential victims and their families, helping them understand and recognize the signs of grooming. Additionally, counseling plays a key role in victim recovery, offering psychological support to overcome the lasting impacts of abuse. This research underscores the need for proactive measures and comprehensive guidance and counseling strategies to address child grooming effectively.